Quaternary ice thinning of David Glacier in the Terra Nova Bay region, Antarctica - Rhee, Hyun Hee; Lee, Min Kyung; Seong, Yeong Bae; Lee, Jae Il.; Yoo, Kyu-Cheul; Stutz, Jamey; Yu, Byung Yong (Elsevier BV, 2022)
Understanding the history of Antarctic glaciation is important for interpreting paleoclimatic changes and estimating the changes in climate, sea level, and ice volume in the future. Ice core studies of the East Antarctic Ice Sheet (EAIS) and marine sediment cores from the entire Ross Sea have employed numerous proxies to reconstruct the glacial history of the Antarctic region. However, the ice and marine core records can be biased because of their specific locations, such as the uppermost accumulation zone or the terminus of the ablation zone, thereby introducing significant uncertainties in ice modeling. In this study, we analyzed 34 new Be-10 and Al-26 samples from four benches that were glaciated in the past by David glacier and incorporate the present ice-free flat surfaces. We suggest that the David glacier experienced monotonic and stepwise vertical lowering along the flanks of Mt. Priestley since the early Pleistocene. The uppermost bedrock benches on Mt. Priestley were exposed at 1.77 +/- 0.32 Ma, with no evidence of subsequent overriding by readvancing ice. At Mt. Priestley, the David glacier has been characterized by a cold-based regime since 1.77 Ma, with a denudation rate of only similar to 16 cm/Ma, corresponding to the regional transition from warm to cold-based glaciation at 3.5 Ma. Simple exposure ages from two lower benches date to Marine Isotope Stage (MIS) 7 (234.1 +/- 13.1 ka; 545 m asl) and MIS 4 (64.8 +/- 13.7 ka; 222 m asl), suggesting that, since MIS 8, the overall lowering of glaciers has remained monotonic. The upper bench marks the lower limit of the MIS 8 glacial period and the upper limit of Penultimate Glacial Maximum (MIS 6), while the lower landform defines the upper limit of the last glacial period (MIS 4-2). The magnitude of Quaternary ice thinning at the David glacier was the highest (similar to 990 m) in the present terminal area (i.e., the most sensitive ablation zone), in contrast to the other outlet glaciers draining into the Terra Nova Bay, which experienced less ice lowering. The combination of the terrestrial (in situ Be-10 and Al-26) and previous marine (authigenic Be-10) cosmogenic data used in our study document the history of lowering of the David glacier driven by climatic changes during the Pleistocene. Both deglaciation and glaciation were limited during the mid-Pleistocene transition (MPT) and prior to the mid-Bruhnes event (MBE), due to the prevailing cold and arid climate, whereas deglaciation was dominant during other warm periods.